Digital human dynamics in socio-educational contexts: a review of evidence from scales - Martínez Cañestro, Hugo Antonio; Megías Torres, María del Mar; Martínez Lentisco, María del Mar; Alonso López, Isabel Damiana (Frontiers in Human Dynamics, 2026)
Social media use has become integral to daily life, raising increasing concern about its addictive potential, particularly among adolescents. This mini-review combined a structured systematic search and complementary narrative exploration to identify and analyze 27 validated instruments assessing social media addiction. The first phase followed PRISMA-based criteria across four databases (Scopus, Web of Science, PubMed, Redalyc), while subsequent phases expanded the search to include related and recent literature up to 2025. The instruments encompass physiological, behavioral, cognitive–emotional, and social dimensions of addiction—such as tolerance, withdrawal, preoccupation, mood modification, and time displacement—and were validated in both Western and non-Western contexts. Western-developed scales (e.g., BSMAS, SMD Scale) demonstrated stronger psychometric consistency and larger samples, whereas regional adaptations improved cultural relevance but require broader validation. The absence of unified diagnostic criteria continues to limit cross-cultural comparison. These findings underscore the need for internationally standardized and culturally sensitive tools to improve early detection and cross-context comparability in adolescent social media addiction research.